Effects of Drying Methods on Quality Characteristics and Flavor of Dried Apples - Juan SONG; Haiyan ZHANG; Chaozhen ZENG; Jing YUAN; Yuwen MU; Sanjiang KANG; Pengcheng WEN (Shipin gongye ke-ji, 2024)
To investigate the processing methods that could improve the quality of Jingning dried apple snacks, the effects of five drying methods (hot air drying, solar drying, vacuum freeze drying, microwave-pressure puffing drying, and heat pump drying) on energy consumption, antioxidant activity, microstructure, and flavor of dried apples were studied. The results showed that compared with the other four drying methods, in terms of energy consumption that vacuum freeze drying had the highest unit energy consumption (69.48±1.69 kW·h/kg), while solar drying had the lowest unit energy consumption (19.60±1.36 kW·h/kg). In terms of hardness and crispness, dried apples that were dried by hot air drying were found to have the highest levels of hardness and lowest levels of crispness, while those that were dried by vacuum freeze drying were found to have the lowest levels of hardness and a higher degree of crispness. In terms of colour difference, vacuum freeze drying had the highest L* value (72.91±0.59) and the ΔE value was closest to the fresh samples (10.48±0.30). In addition, compared with fresh samples, vacuum freeze drying effectively slowed down the loss of antioxidant activity of dried apples, with the contents of ascorbic acid, total phenols and total flavonoids decreased by 35.22%, 39.27% and 32.02%, respectively. Meanwhile, the total antioxidant capacity, hydroxyl radical scavenging rate and superoxide anion scavenging rate decreased by 23.50%, 57.24% and 10.56%, respectively. In terms of microstructure, the cell layer of dried apples with vacuum freeze drying preserved a regular sponge-like porous structure with good texture. In terms of flavor, 96 volatile substances were identified in five types of dried apples, while it made the dried apples with vacuum freeze drying more aromatic and richer in taste. In conclusion, vacuum freeze drying is recommended as a method to improve the quality and flavor of high-quality dried apples, and provides significance in guiding the industrialized production of dried apple products.